REAL-TIME SMS TRANSMISSION USING WEBSOCKET WITH END-TOEND ENCRYPTION (E2EE). - GUNASEKAR, M.; DHINESH, V.; DHISWANTH, N.; REVANTH, R.; VIGNESH, G. SRI (Turkish Journal of Physiotherapy Rehabilitation, 2021)
With the development in communication technology, real time messaging is improved to greater levels. We transformed from sending letters to Electronic mail in two decades. And with the addition of smartphones, sending someone a message is extremely fast. These smartphones questioned privacy in the beginning stage. Thats when encryption comes into play. However we still receive important information like One Time Password (OTP) to our cellular inbox and not in WhatsApp or Facebook messenger. When we travel to different places we usually take our cellular sim card in order to get things done. But we cannot be so sure that the country we travel to have a good network coverage for our cellular. Even if it's present we end up paying more than we pay in our native country. Hence cellular sms must be transmitted over the internet. With the help of websockets we can send and receive cellular sms with low latency. All we need is a smartphone and access to the internet. The cellular sms is sent using one smartphone and received by another so that we can be free of additional charges charged by other countries.